On-chip SRR and CSRR for millimeter-wave integrated systems: Review and applications. (January 2023) - Yang, Ke; Liang, Yuan; Zhang, Hao Chi; Feng, Guangyin
Abstract: On-chip metadevices have been developed in progress aiming to generate extraordinary performance over conventional components in millimeter-wave (mmW) realms, and their full integration with advanced complementary-metal-oxide-semiconductor (CMOS) circuits pave a new way toward miniature and high-performance integrated systems. This article aims to provide a general overview of split-ring resonators (SRRs) and complementary split-ring resonators (CSRR), from the perspective of fundamental physics, recent progress of on-chip implementations, and their impacts on the development of mmW integrated circuits and systems. SRR/CSRR-based metadevices are discussed in terms of their design challenges, methods, implementation, and testing results. In particular, their applications to CMOS oscillators, modulator and signal source are highlighted. Finally, using the SRR/CSRR, a number of examples are provided to showcase the recent advances of integrated systems toward mmW communication and imaging. Future directions enabled by SRR and CSRR will be envisioned.